School dropout in middle-level technical vocational education: an in-depth look at two major villains - the lack of information and the lack of technical education identity (Research, Society and Development, 2019)
The professional technical education of medium level has experienced in the last years wide expansion in the offer of vacancies, however, this process has been accompanied by an old known problem - the phenomenon of school dropout. In this sense, it is believed that it is necessary to know the elements that contribute to this problem being maintained; because understanding the problem is the best way to think of strategies to deal with avoidance. The aim of this article is to analyze the possible measures to be adopted to minimize the phenomenon of evasion in technical secondary education. The article presents a qualitative approach on the situation of school dropout, and a simplified diagnosis was developed through bibliographical research on the relevant aspects that have contributed to the technical education students abandoning their courses, as well as an attempt to understand What can be done. Throughout the work, we tried to interpret the problem through the bibliography of important authors such as, for example, Rosemary Dore, who currently, in the Brazilian educational scene, has been dedicated to understand the phenomenon of school dropout in the specificities of technical vocational education of medium level. It was identified in this study that the absence of information has made it difficult to confront and minimize the effects of the problem, and also that the lack of technical education has contributed to the young people giving up their courses. It is concluded that further research on evasion in the area of technical education is necessary, and especially the need for technical training to have its own identity and that one of the ways of constructing this identity is a type of integral training and humanized, far from the idea of training merely submissive to the labor market.